2008
DOI: 10.1109/led.2007.915374
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Enhancement-Mode InAs Nanowire Field-Effect Transistor With 50-nm Wrap Gate

Abstract: Abstract-We present results on fabrication and dc characterization of vertical InAs nanowire wrap-gate field-effect transistor arrays with a gate length of 50 nm. The wrap gate is defined by evaporation of 50-nm Cr onto a 10-nm-thick HfO 2 gate dielectric, where the gate is also separated from the source contact with a 100-nm SiO x spacer layer. For a drain voltage of 0.5 V, we observe a normalized transconductance of 0.5 S/mm, a subthreshold slope around 90 mV/dec, and a threshold voltage just above 0 V. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(118 citation statements)
references
References 16 publications
(8 reference statements)
5
110
2
1
Order By: Relevance
“…As compared to previously published data [2,9], we note a larger subthreshold slope in these devices, 120 mV/decade as compared to 80 mV/decade. This can mainly be attributed to insufficient scaling of the wire diameter for this gate length, but also a high D it .…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…As compared to previously published data [2,9], we note a larger subthreshold slope in these devices, 120 mV/decade as compared to 80 mV/decade. This can mainly be attributed to insufficient scaling of the wire diameter for this gate length, but also a high D it .…”
Section: Resultssupporting
confidence: 67%
“…The NW FETs are fabricated from epitaxially grown InAs nanowires with a diameter of 40 nm, grown on an <111>-B InAs substrate [2,9]. The wires are Sn-doped with a molar fraction of 3.49x10 -8 .…”
Section: Device Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…The device exhibits enhancement mode operation (V T = 0.29 V) and combines competitive on-performance, as shown by the peak transconductance (g m,max ) of 0.64 mS μm −1 , and off-performance, characterized by the minimum sub-threshold swing (SS) of 90mV/decade at V DS = 0.5 V. For an off-current (I off ) of 100 nA μm −1 and a supply voltage of 0.5 V, the device exhibits an on-current (I on ) of 0.14 mA μm −1 . This device performance is competitive to earlier published works on vertical III-V nanowire MOSFETs [5], [11]- [13]. The good sub-threshold behavior is attributed to the fabrication method, which allows an unintentionally doped channel.…”
Section: Device Fabricationmentioning
confidence: 50%
“…For example, studies of nanowire FETs fabricated from boron and phosphorus-doped Si nanowires have shown that the devices can exhibit performance comparable to the best reported value for planar devices made from the same materials [Cui et al, 2003]. Studies have also demonstrated the high electron mobility of epitaxial InAs nanowire FETs with a wrap-around cylindrical gate structure surrounding a nanowire [Thelander et al, 2008]. Moreover, the change in conductance of semiconductor wires as a function of gate voltage can be used to determine the conductive type of a given wire since the conductance will vary oppositely for increasing positive and negative gate voltages [Cui et al, 2003].…”
Section: P-type Zno:p Microwire Fetmentioning
confidence: 93%